Flux density monitoring of extragalactic radio sources. Observations at 22, 37 GHz and 102 MHz within the research programs for the RT-22 CrAO and the Odesa Observatory "URAN-4" IRA NASU - Volvach, A.E.; Ryabov, M.I. (Кинематика и физика небесных тел, 2005)
Observations of the millimeter wave emission variability of extragalactic radio sources may give an important information on active processes in their inner parts. The millimeter wave observations of extragalactic radio sources were started with the 22-m radio telescope of the Crimean Astrophysical Observatory in 1973. Since 1973, over 10 000 observations of 140 sources have been obtained. As the extended monitoring programs have demonstrated, there are unpredictable outbursts, quiescent periods, minimum flux levels, and secular trends. As it follows from the analysis, the flare evolution can be divided in three phases: (1) a rapid flux increase; (2) a plateau when the flux relatively constant; (3) a slow intensity decrease. Significant differences in the flare evolution in various optical classes of radio sources were not found. The Odesa Observatory of the Institute of Radio Astronomy of NAS of Ukraine (IRA NASU) have performed a long-term flux monitoring of extragalactic radio sources at 102 MHz with the DKR–1000 radio telescope of the Pushchino Radio Astronomy Observatory of the Astro–Space Center of the Lebedev Physical Institute. About 20 observational sessions of over 80 compact and extended radio sources have been carried out in 1984–1985, 1988–1992, and 1996–1998. The variability of radio sources at meter wavelengths is caused by “scintillations” of the flux density of the inhomogeneity of the local interstellar medium. At the same time, many of sources are showed anomalous flux variations at meter wavelengths that do not correspond to the assumption about interstellar scintillations. In this paper, we present a comparison of the data of two independent observations programs. Own activity of radio sources has been taken into account and the flux variability with the time delay at millimeter and meter wavelengths has been considered. It was possible due to the longer time series of the RT-22 observations.